REGULASI HUKUM DALAM MENANGANI KONTEN DIGITAL NEGATIF (TIDAK MENDIDIK) DAN DAMPAKNYA TERHADAP ANAK DITINJAU DARI PERSPEKTIF MAQASID SYARI’AH - Siti Jauhariatul Masruroh; Atun Wardatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology brings both benefits and challenges, particularly for children who are vulnerable to the negative impacts of non-educational digital content. Content containing elements of violence, pornography, hate speech, and misleading information can significantly affect children's moral and intellectual development. Therefore, strong legal regulations are needed to protect children from these harmful effects. This study aims to analyze the legal regulations governing non-educational digital content in Indonesia and how the law addresses its impact on children from the perspective of Maqāṣid al-Syarī‘ah. The research method used is normative juridical research with a statutory approach. The findings indicate that existing regulations, such as the Child Protection Law and the Electronic Information and Transactions Law (UU ITE), still have loopholes in monitoring and law enforcement against harmful digital content. From the perspective of Maqāṣid al-Syarī‘ah, protecting children from negative content is closely related to safeguarding life (hifẓ an-nafs), intellect (hifẓ al-‘aql), and lineage (hifẓ an-nasl). Therefore, synergy between the government, society, and digital platforms is needed to strengthen policies and digital literacy to create a safer digital environment for children.